Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec - Sucha, E.; SIlva, E.; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)
fs-ref-orig: Sucha, E., SIlva, E., Batista, R., & Bouchard, L. (2014). Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec. Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa. fs-code-orig: Sucha-2014a

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)
fs-ref-orig: Sucha, E., SIlva, E., Batista, R. et Bouchard, L. (2014). Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec. Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa. fs-code-orig: Sucha-2014b